1934
DOI: 10.1080/00378941.1934.10834027
|View full text |Cite
|
Sign up to set email alerts
|

Sur la valeur taxinomique de l'Agropyrum acutumRoehm. et S.—Contrôle cytologique

Abstract: Cl'th• {•tude morphologique montre qur l'A. amtum est bien appa-rniHt'• aux A. junr'l'li/Jl ct J\. pungens; un e<•rtain nornhn• de ses earac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1937
1937
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…There is evidence of the limited success of pentaploids in other groups. In Agropyron spp,, for example, there are Agropyron diivalii [zn = 35, 42) (Simonet, 1935), the hybrid species A. acutum {zn = 35) (Simonet, 1934) and the natural hybrid A. ensyiix A. scabrum {zn = 35) (Connor, 1956). It can be recalled that one of our most important fibreproducing plants Agave sisalana {zn = 149) is also pentaploid (Granick, 1944), There are many other reports of pentaploids or other uneven polyploids, particularly in the grasses, but in most cases they are seed-producing apomicts which are not strictly comparable with H. mollis.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of the limited success of pentaploids in other groups. In Agropyron spp,, for example, there are Agropyron diivalii [zn = 35, 42) (Simonet, 1935), the hybrid species A. acutum {zn = 35) (Simonet, 1934) and the natural hybrid A. ensyiix A. scabrum {zn = 35) (Connor, 1956). It can be recalled that one of our most important fibreproducing plants Agave sisalana {zn = 149) is also pentaploid (Granick, 1944), There are many other reports of pentaploids or other uneven polyploids, particularly in the grasses, but in most cases they are seed-producing apomicts which are not strictly comparable with H. mollis.…”
Section: Discussionmentioning
confidence: 99%
“…junceiforme and E. repens (Heneen, 1962, 1963b). In addition, Simonet (1934) already attributed a hybrid origin to certain samples between A. littorale (= E. pycnantha ) and A. littoreum (= E. repens ), based on their intermediate morphology. He differentiated them by their leaves, which are planar, flat and green in E. repens , but glaucous, tightly inrolled and subulated at the tip in E. pycnantha , and at the level of a subtetragonal ear in E. pycnantha .…”
Section: Discussionmentioning
confidence: 99%
“…This latter species was not recognized by Dewey (1984). According to the taxonomic diagnoses, the samples described under E. pungens would in some cases correspond to E. pycnantha and in other cases to E. repens or to hybrid forms (Simonet, 1934; Kerguelen, 1975).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural interspecific hybrids in Agropyron were studied in Europe (Simonet 1934(Simonet , 1935Ostergren 1940a, b ;Godley 1951 and others), in New Zealand (Conner 1956(Conner , 1957 and in North America (Dewey 1963). In the present study, two natural hybrids are reported involving one tetraploid, Ag.…”
Section: Discussionmentioning
confidence: 99%